2011
DOI: 10.1111/j.1834-7819.2011.01358.x
|View full text |Cite
|
Sign up to set email alerts
|

Higher concentration local anaesthetics causing prolonged anaesthesia. Do they? A literature review and case reports

Abstract: Higher concentration dental local anaesthetics (3% and 4%) have become more available in Australia in recent years. Benefits claimed include a faster onset of anaesthesia and improved success with injections compared to 2% solutions. Recent reports suggest that the higher concentration carries a greater risk of prolonged anaesthesia to the mandibular and particularly the lingual nerves. The literature was reviewed and those studies which demonstrated adverse effects of different concentrations of local anaesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Some studies have demonstrated no evidence of injury to the nervous structure (Baroni et al 2013, Rogers et al 2014, whereas others have shown increased risk of neurotoxicity (presenting as paraesthesia) related to the use of 4% articaine for regional blocks (e.g. inferior alveolar) (Haas & Lennon 1995, Hillerup & Jensen 2006, Garisto et al 2010, Kingon et al 2011. One potential limitation of the study might be that all inferior alveolar nerve blocks were administered using 4% articaine with 1 : 100 000 epinephrine hydrochloride.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated no evidence of injury to the nervous structure (Baroni et al 2013, Rogers et al 2014, whereas others have shown increased risk of neurotoxicity (presenting as paraesthesia) related to the use of 4% articaine for regional blocks (e.g. inferior alveolar) (Haas & Lennon 1995, Hillerup & Jensen 2006, Garisto et al 2010, Kingon et al 2011. One potential limitation of the study might be that all inferior alveolar nerve blocks were administered using 4% articaine with 1 : 100 000 epinephrine hydrochloride.…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly local anaesthesia is the technique employed but this is not without complication. [2][3][4] The objectives of exodontia are clear cut; to remove the whole tooth whilst preserving the alveolus for future prosthetics or implants. Again it is all too easy for the inexperienced dentist and their patient to emphasise the removal of the whole tooth at the expense of the alveolus.…”
Section: Techniquementioning
confidence: 99%
“…6 A review of the literature revealed only two similar cases occurring following administration of an inferior dental block. Torrente-Castells et al 7 reported a case involving a 10-year-old girl who received an inferior alveolar nerve block using one cartridge of 4% articaine with 1:200 000 adrenaline.…”
Section: Discussionmentioning
confidence: 99%